The The Identity of Demak: Unveiling Culture, Architecture, Heritage and Historical Significance (International Journal of Architecture and Urbanism, 2023)
The concept of local identity, known as "jati diri," has gained prominence as a means of understanding and preserving the unique cultural and historical characteristics of cities. This paper focuses on exploring the jati diri of Demak, a city in Indonesia with rich cultural heritage, architecture and historical significance. Through an interdisciplinary approach encompassing history, culture, architecture, and community engagement, this study aims to uncover the essence of Demak's identity, highlighting its historical evolution and contemporary manifestations.The paper delves into the historical context of Demak, tracing its origins from a powerful maritime trading kingdom to its role as a center of Javanese culture and Islamization. By examining historical records, archaeological findings, and oral traditions, the study seeks to identify the key events and socio-cultural dynamics that have shaped Demak's unique identity over the centuries.Furthermore, the research investigates the role of cultural elements, including traditional art forms, rituals, architecture, and local practices, in contributing to Demak's identity. Through fieldwork, interviews with local experts, and analysis of cultural artifacts, the paper aims to capture how Demak's distinctive culture is woven into the fabric of everyday life and community interactions.The study also addresses the challenges of preserving Demak's identity in the face of modernization, urban development, and globalization. It discusses the efforts undertaken by local communities, cultural organizations, and governmental bodies to safeguard Demak's heritage and promote awareness of its identity. City Government can help to build a stronger resource structure (Fahmi & Haryanto, 2020).In conclusion, this paper sheds light on the significance of Demak's jati diri as a vital component of its cultural landscape. By unraveling the historical, socio-cultural, and architectural layers that define the city, the study contributes to a comprehensive understanding of Demak's identity. The findings provide insights into the importance of preserving and celebrating local heritage, serving as a case study for other cities seeking to maintain their unique identities amidst the currents of change.